2015
DOI: 10.1128/jvi.01955-15
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of HLA-B*13-Associated Escape Mutations on HIV-1 Replication and Nef Function

Abstract: HLA-B*13 is associated with superior in vivo HIV-1 viremia control. Protection is thought to be mediated by sustained targeting of key cytotoxic T lymphocyte (CTL) epitopes and viral fitness costs of CTL escape in Gag although additional factors may contribute. We assessed the impact of 10 published B*13-associated polymorphisms in Gag, Pol, and Nef, in 23 biologically relevant combinations, on HIV-1 replication capacity and Nef-mediated reduction of cell surface CD4 and HLA class I expression. Mutations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 76 publications
3
19
1
Order By: Relevance
“…For each participant, three nef sequences were isolated from baseline plasma HIV RNA, cloned into a green fluorescent protein (GFP) reporter plasmid using previously described methods (36,38,45), and confirmed to cluster with their respective bulk plasma HIV RNA nef sequence (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…For each participant, three nef sequences were isolated from baseline plasma HIV RNA, cloned into a green fluorescent protein (GFP) reporter plasmid using previously described methods (36,38,45), and confirmed to cluster with their respective bulk plasma HIV RNA nef sequence (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…While Nef is a critical virulence factor in HIV infection (Kestler et al, 1991) and highly immunogenic (Radebe et al, 2011), it is also highly variable and largely excluded from the leading conserved T-cell based vaccine immunogens in testing (Borthwick et al, 2014;Mothe et al, 2015). Nevertheless, growing evidence suggests that a limited number of mutations in Nef, particularly specific mutation combinations, can impair the virus Shahid et al, 2015;Ueno et al, 2008), and that CTL targeting of selected Nef epitopes could lead to better clinical outcome (Adland et al, 2013). In the present analysis, two HLA-associated polymorphisms, 71K and 108D, were associated with decreased ability of Nef to inhibit TCR-mediated NFAT signalling.…”
Section: Discussionmentioning
confidence: 99%
“…Shahid et al . demonstrated that HLA‐B*13 has a protective role for HIV infection by escape mutations on HIV‐1 replication and Nef function in a Caucasian population (Shahid et al, ). Zhang.…”
Section: Discussionmentioning
confidence: 99%
“…has not been reported as one of the genetic factors for HCV infection in previous studies, it has been reported to be associated with HIV infection. Shahid et al demonstrated that HLA-B*13 has a protective role for HIV infection by escape mutations on HIV-1 replication and Nef function in a Caucasian population(Shahid et al, 2015).Zhang. et al showed that HLA-A * 30-B * 13-C * 06 contributes to the slow progression of HIV infection in the northern Chinese.…”
mentioning
confidence: 99%